2012
DOI: 10.1371/journal.pone.0050920
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Requirement for BMP9 Signaling in Endothelial Cells Reveals New Mechanism of Action for Selective Anti-Endoglin Antibodies

Abstract: Endoglin (ENG), a co-receptor for several TGFβ-family cytokines, is expressed in dividing endothelial cells alongside ALK1, the ACVRL1 gene product. ENG and ACVRL1 are both required for angiogenesis and mutations in either gene are associated with Hereditary Hemorrhagic Telangectasia, a rare genetic vascular disorder. ENG and ALK1 function in the same genetic pathway but the relative contribution of TGFβ and BMP9 to SMAD1/5/8 activation and the requirement of ENG as a co-mediator of SMAD phosphorylation in end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 51 publications
(73 reference statements)
4
87
1
Order By: Relevance
“…Also, in clinical development as an antitumor agent is a chimeric antibody (TRACON) capable of neutralizing endoglin (CD105; ref. 31), a proangiogenic protein in the TGFb superfamily that binds BMP9/BMP10 (22,45,46), with loss-of-function mutations resulting in another type of vascular dysplasia, HHT-1 (15,47). In patients with advanced, refractory tumors (31), anti-endoglin antibody was associated with infusion reactions and immunogenicity distinct from effects described for dalantercept in the present study, whereas other adverse effects such as anemia and telangiectasias were observed in both studies.…”
Section: Discussionmentioning
confidence: 37%
“…Also, in clinical development as an antitumor agent is a chimeric antibody (TRACON) capable of neutralizing endoglin (CD105; ref. 31), a proangiogenic protein in the TGFb superfamily that binds BMP9/BMP10 (22,45,46), with loss-of-function mutations resulting in another type of vascular dysplasia, HHT-1 (15,47). In patients with advanced, refractory tumors (31), anti-endoglin antibody was associated with infusion reactions and immunogenicity distinct from effects described for dalantercept in the present study, whereas other adverse effects such as anemia and telangiectasias were observed in both studies.…”
Section: Discussionmentioning
confidence: 37%
“…Thus, endoglin may play a role in BMP signaling during angiogenesis. In support of this view, endoglin is necessary for BMP9 signaling in ECs involved in angiogenesis [151], and the blockade of BMP9 binding to ALK1 prevents endoglin binding to ALK1 and the subsequent angiogenic response [149].…”
Section: Endoglin Expression Modifies Angiogenesis and Vascular Remodmentioning
confidence: 96%
“…BMP9 signals through the endoglin/ALK1 complex, and anti-ALK1 antibodies prevent the formation of the BMP9/ALK1/endoglin complexes and attenuate BMP9-dependent signaling and sprouting [149]. Additionally, endoglin appears to be necessary for BMP9 signaling through ALK1 in HUVECs, in which TGF-β is unable to activate Smad1/5/8 signaling on its own [151]. Similarly, contradictory findings regarding the effect of BMPs in angiogenesis have been reported.…”
Section: Endoglin Regulation Of Focal Adhesions During Ec Migrationmentioning
confidence: 99%
“…The predominant type of mutation, the existence of mutation hot spots within the gene, and the effects of the mutations on expression and signaling of the receptor are currently unknown. However, evidence suggests that depletion of endoglin impaired BMP9-induced SMAD1/SMAD5/SMAD8 phosphorylation in human pulmonary artery endothelial cells [150]. Recently we reported that a soluble form of endoglin that may function as an anti-angiogenic ligand trap of BMP9 is present at elevated levels in the circulation of individuals with Group 1 PAH, suggesting an additional mechanism by which abnormalities in this protein may attenuate BMP9 signaling [123].…”
Section: Mutations Of Eng/endoglin In Pah With or Without Hht-1mentioning
confidence: 98%
“…Signaling mediated by BMP9, BMP10, BMPR2, ALK1, and the type III co-receptor endoglin is specialized in the vascular endothelium and in embryonic endocardium owing to high abundance of these components [137]. Evidence suggests that BMPR2, ALK1, and endoglin are required for endothelial cell signaling and/or function in response to BMP9 or BMP10 [33,34,150,205]. …”
Section: Bmp Ligands and Receptors In The Cardiopulmonary Systemmentioning
confidence: 99%